Pediatric Neuro-Ophthalmology - Brodsky, Michael C.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
"Due to the generous representation of the afferent visual system within the brain, neurological disease may disrupt vision as a presenting symptom or as a secondary effect of the disease. Conversely, early developmental disturbances of vision often disrupt ocular motor control systems, giving rise to complex disorders such as nystagmus, strabismus, and torticollis. The signs and symptoms of neurological disease are elusive by their very nature, presenting a confounding diagnostic challenge. Neurological medications and neurosurgical treatments can produce neuro-ophthalmological dysfunction that can be difficult to distinguish from disease progression. Affected patients may experience substantial delays in diagnosis, and are often subjected to extensive (and expensive) diagnostic testing. Scientific articles pertaining to specific disorders are scattered throughout medical subspecialty journals. These children continue to "fall through the cracks" of our medical education system. The increasing recognition that pediatric neuro-ophthalmology comprises a distinct set of diseases from those seen in adults has led to its emergence as a dedicated field of study. "Since the original publication of Pediatric Neuro-Ophthalmology nearly fourteen years ago, interest in the field has burgeoned. Pediatric ophthalmology and pediatric neurology subspecialty conferences often include symposia dedicated to recent advances in pediatric neuro-ophthalmology. Technical advances in neuroimaging have given rise to a more integrated mechanistic classification of neuro-ophthalmological disease in children. Our understanding of neurodevelopmental disorders of the visual system has expanded, longstanding monoliths have been dissembled into component parts, basic molecular mechanisms have taken center stage, and genetic underpinnings have become definitional. Evolutionary alterations can now be observed at the level of the gene, adding a new dimension to our understanding of disease pathogenesis. New classifications now encompass clinically disparate conditions. Descriptive definitions have been supplanted by mechanistic ones, and clinical definitions superseded by genetic ones. Our concept of disease pathogenesis has been revised and in some cases overturned. Bearing witness to these remarkable advancements has compelled me to enhance and expand the first edition of Pediatric Neuro-Ophthalmology into this new and revised one. "In the first edition of this book, our goal was to present the clinical characteristics, diagnostic evaluation, and therapeutic options for the common neuro-ophthalmologic disorders of childhood. In so doing, we designed the book to be provide a narrative journey through the thought processes involved in the clinical management of these disorders. In this edition, I have retained the basic narrative format of original book, while expanding the exploration of these complex visual disorders in the context of the many new scientific advancements and discoveries that have come to light. These conditions are fun to diagnose, fascinating to understand, and gratifying to manage." --from the Preface to the 2nd Edition.
The Apparently Blind Infant -- Congenital Optic Disc Anomalies -- The Swollen Optic Disc in Childhood -- Optic Atrophy in Children -- Transient, Unexplained, and Psychogenic Visual Loss in Children -- Ocular Motor Nerve Palsies in Children -- Complex Ocular Motor Disorders in Children -- Nystagmus in Children -- Torticollis and Head Oscillations -- Neuro-Ophthalmologic Manifestations of Neurodegenerative Disease in Childhood -- Neuro-Ophthalmologic Manifestations of Systemic and Intracranial Disease.
Keywords: Medicine; Neurology; Ophthalmology; Medicine & Public Health; Ophthalmology; Neurology